Testing and Validating Two Morphological Flare Predictors by Logistic Regression Machine Learning - Korsós, M. B.; Erdélyi, R.; Liu, J.; Morgan, H. (Frontiers in Astronomy and Space Sciences, 2021)
Whilst the most dynamic solar active regions (ARs) are known to flare frequently, predicting the occurrence of individual flares and their magnitude, is very much a developing field with strong potentials for machine learning applications. The present work is based on a method which is developed to define numerical measures of the mixed states of ARs with opposite polarities. The method yields compelling evidence for the assumed connection between the level of mixed states of a given AR and the level of the solar eruptive probability of this AR by employing two morphological parameters: (i) the separation parameter $S_{l-f}$ and (ii) the sum of the horizontal magnetic gradient $G_{S}$. In this work, we study the efficiency of $S_{l-f}$ and $G_{S}$ as flare predictors on a representative sample of ARs, based on the SOHO/MDI-Debrecen Data (SDD) and the SDO/HMI - Debrecen Data (HMIDD) sunspot catalogues. In particular, we investigate about 1000 ARs in order to test and validate the joint prediction capabilities of the two morphological parameters by applying the logistic regression machine learning method. Here, we confirm that the two parameters with their threshold values are, when applied together, good complementary predictors. Furthermore, the prediction probability of these predictor parameters is given at least 70% a day before.